2020
DOI: 10.1002/tax.12363
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the phylogenetic position of the ditypic genus Froriepia reveal Yildirimlia, a new genus of Apiaceae

Abstract: Froriepia is a ditypic genus in the subfamily Apioideae. Froriepia subpinnata occurs in Iran and the Caucasus, while F. gracillima is a species endemic to Turkey that is known only from the type specimen collected near the country's eastern border. Although many comprehensive phylogenetic studies of members of the family Apiaceae have been conducted, the phylogenetic position of Froriepia has remained unknown. When we examined this genus in detail, we suspected that the two species assigned to it may in fact b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The conflict between the results regards the position of tribe Careae, which is resolved as sister to tribe Pyramidoptereae in the ITS tree, but is nested into it in the rps16 tree. This result is congruent with that inferred by a recent study using rps16 sequences (Doğru‐Koca et al 2020) based on a smaller data set. It should be noted, however, that the overall resolution and branch support in the rps16 tree is much lower than in the ITS tree because of lower variability of the plastid sequences.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The conflict between the results regards the position of tribe Careae, which is resolved as sister to tribe Pyramidoptereae in the ITS tree, but is nested into it in the rps16 tree. This result is congruent with that inferred by a recent study using rps16 sequences (Doğru‐Koca et al 2020) based on a smaller data set. It should be noted, however, that the overall resolution and branch support in the rps16 tree is much lower than in the ITS tree because of lower variability of the plastid sequences.…”
Section: Resultssupporting
confidence: 92%
“…According to a BLAST search in the GenBank database (<http://www.ncbi.nlm.nih.gov>), Carum atlanticum demonstrate affinity within the tribe Pyramidoptereae, whereas C. proliferum , C. jahandiezii and C. lacuum fall within the tribe Apieae. To determine more precisely the phylogenetic position of the studied species, the published nrITS datasets from Zakharova et al (2012), Fernández Prieto and Cires (2014), Jiménez‐Mejías and Vargas (2015) and Doğru‐Koca et al (2020) were modified and used. The final set of samples was increased to include representatives of the tribe Careae, which comprises the generitype Carum carvi , and the Conioselinum chinense Clade, which includes Meum athamanticum connected with Carum atlanticum in its taxonomic history.…”
Section: Methodsmentioning
confidence: 99%
“…Individual plastid markers (intron sequences of rps16 , rpl16 , rpoC1 genes) often did not show sufficient variability to provide resolution both within the Tordylieae and between the adjacent tribes or produced trees incongruent with the nrITS phylogeny [ 35 , 49 , 50 ]. A recent plastid phylogenomic investigation claimed new robust evidence for incongruence between the nuclear genome and plastome evolution in Tordylieae [ 20 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…and Oedibasis Koso-Pol., with an outside position from all other Saniculoideae . Finally, Doğru-Koca et al 41 from a phylogenetic point of view suggested that Froriepia K.Koch should be the sister genus of Lagoecia cuminoides , and although both genera belong to the same tribe ( Piramidoptereae ), they are morphologically very different from each other. Even if the collocation of the genus Lagoecia is complex, from a morpho-taxonomic point of view Lagoecia should be considered very close to Petagnia , having in common a specific character: the abortion of an ovarian lodge 21 and the consequent maturation of a single achene.…”
Section: History Taxonomy Nomenclature and Morphologymentioning
confidence: 99%